A carboxylate- and pyridine-based organic anode material for K-ion batteries. (23rd September 2022) - Holguin, Kathryn; Qin, Kaiqiang; Huang, Jinghao; Luo, Chao
Abstract : In this work, a new carboxylate- and pyridine-based organic anode material was exploited in K-ion batteries. The results demonstrate the critical role of multiple active centers (CO and CN) in one molecule to enhance the electrochemical performance. Abstract : Developing high-capacity, stable, and sustainable K-ion batteries (KIBs) is an ongoing challenge due to the lack of high-performance and environmentally benign electrode materials. To address this challenge, organic electrode materials that are affordable, abundant, highly sustainable, highly tunable and flexible offer opportunities. Herein, we report a novel N-containing carboxylate salt, K2 C12 H6 N2 O4 (K-DCA), with two bipyridine moieties and two carboxylate groups. The carboxylate- and pyridine-based active centers in K-DCA can reversibly react with four K-ions to provide a specific capacity of 163.3 mA h g −1 with a pair of redox plateaus centered at ∼0.8 V. When coupling with nitrogen-doped reduced graphene oxide (NrGO), the composite anode material, K-DCA-NrGO, demonstrates a high specific capacity of 225.25 mA h g −1 and increased capacity retention during long-term cycling. Additionally, the reaction kinetics and mechanism studies demonstrate that the composite exhibits low overpotentials, low interphase resistance, a partial pseudo-capacitance behavior, and stable chemical/morphological structures upon cycling, which contribute to the fast kinetics and long cycle life.